2017
DOI: 10.1111/tops.12264
|View full text |Cite
|
Sign up to set email alerts
|

Structure Mapping for Social Learning

Abstract: Analogical reasoning is a foundational tool for human learning, allowing learners to recognize relational structures in new events and domains. Here I sketch some grounds for understanding and applying analogical reasoning in social learning. The social world is fundamentally characterized by relations between people, with common relational structures-such as kinships and social hierarchies-forming social units that dictate social behaviors. Just as young learners use analogical reasoning for learning relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Indeed, although our emphasis here has been on children's understanding of false belief, the same analogical comparison processes might support children's understanding of diverse desires, and perhaps other insights as well. This idea is consistent with research that emphasizes the role of structure-mapping mechanisms in social cognitive development (Christie, 2017;Gerson, 2014).…”
Section: Limitations and Future Directionssupporting
confidence: 90%
“…Indeed, although our emphasis here has been on children's understanding of false belief, the same analogical comparison processes might support children's understanding of diverse desires, and perhaps other insights as well. This idea is consistent with research that emphasizes the role of structure-mapping mechanisms in social cognitive development (Christie, 2017;Gerson, 2014).…”
Section: Limitations and Future Directionssupporting
confidence: 90%
“…There is extensive evidence that children's number and mathematics learning is aided by comparison (Mix, Smith, & Crespo, 2019; Thompson & Opfer, 2010, see reviews by Richland & Begolli, 2016; Richland & Simms, 2015). In the domain of social cognition, recent work shows that children's false belief understanding is facilitated by comparison (Hoyos, Horton, Simms, & Gentner, 2020; see Christie, 2017 for a review). A recently published edited book highlights the importance of comparison in many domains of learning (Childers, 2020).…”
Section: Comparison Fosters Learningmentioning
confidence: 99%
“…Such social comparison results in the evaluation of self, just as it does in adult settings (Festinger, 1954; see recent reviews Gerber, Wheeler, & Suls, 2018; Baldwin & Mussweiler, 2018). But beyond self‐evaluation and/or self‐identity, comparison among social agents—either between self and others or among others—may also result in learning about the social world, including learning about social relations and roles (for review, see Christie, 2017). For example, a recent study showed that four‐year‐olds had a better Theory of Mind understanding after comparing others' thoughts (Hoyos et al, 2020).…”
Section: Comparison During Playmentioning
confidence: 99%
“…The collaborative learning approach could result in individual social and cognitive development and change, as this approach encourages intercultural interaction while managing projects and producing quality outcomes (Heyes, 2016;Christie, 2017;Kendal, Boogert, Rendell, Laland, Webster & Jones, 2018;Wangi et al, 2018). In a multicultural higher education environment, such as the module in which this research is conducted, every student can make a unique contribution to a group project (Silalahi, 2019).…”
Section: Background To the Studymentioning
confidence: 99%